Prevalence of overactive bladder symptoms and urinary incontinence in a tertiary care hospital in Egypt - Bahloul, Mustafa; Abbas, Ahmed M.; Abo-Elhagag, Mervat A.; Elsnosy, Elwani; Youssef, Alaa-eldein A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The current study aims to estimate the prevalence of Overactive bladder (OAB) and urinary incontinence (UI) among women attending Assiut Woman’s Health Hospital. Additionally, to explore the impact of UI and OAB on The Quality of Life (QOL) of women. Methods: A population-based survey included participants aged 18 years and older selected from Assiut Woman’s Health Hospital and received The Bristol Female Lower Urinary Tract Symptoms Questionnaire (BFLUTSQ). OAB was defined in to two versions using the international continence society (ICS) definition of 2002 as either urgency sometimes or more alone (OAB1) or urgency sometimes or more with frequency more than eight times per day and /or nocturia once or more per night (OAB2). Incontinence and other LUTS were positive if answer scores ≥2 to BFLUTSQ question for incontinence and other LUTS. Results: The total prevalence of OAB was 39.0% (351 women). The prevalence of OAB dry and OAB wet was 26% (234 women) and 13% (117 women), respectively, which suggested that 66.7% suffer from OAB dry and 33.3% suffer from OAB wet. The prevalence of dry OAB is significantly higher than wet OAB. The overall prevalence of UI was 22.2% (201 women). The prevalence of stress UI, urge UI and mixed UI was 5.7%, 5.1% and 11.4%, respectively. Conclusions: OAB symptoms and UI are highly prevalent. Furthermore, both of them have severe effects on daily and sexual life as well as being related to psychological symptoms such as anxiety and depression.